How Students Perceive Professional Competencies in Software Projects: A Cyclical Study on Human Behavior in Business Process Management Context - Vilela, Jéssyka (Anais do Workshop em Modelagem e Simulação de Sistemas Intensivos em Software (MSSiS), 2025)
Context: Computing education must go beyond technical training to encompass the development of professional competencies. Objective: This paper aims to characterize the evolution of students’ perceptions regarding the importance and difficulty of four professional competencies throughout a semester-long integrated project involving three disciplines: Business Process Management (BPM), project management, and enterprise management systems. Method: Forty-seven undergraduate students worked in multidisciplinary teams to solve real-world problems using Business Process Management Notation (BPMN) and interface prototyping. At the end of each of the four project cycles, students assessed the perceived importance and difficulty of teamwork, project planning, client negotiation, and technical challenges. The results showed that while students consistently rated all competencies as highly important, they perceived increasing difficulty over time, particularly in teamwork and project planning. This trend indicates a growing awareness of the complexity of non-technical skills. Conclusions: The use of cyclical self-assessment effectively revealed behavioral patterns and learning needs, offering valuable insights into human behavior in software education and supporting more integrated curriculum strategies.